Resubmission of bank guarantee and expenditure program against advance payment - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding resubmission of bank guarantee and expenditure program against advance payment of BRAC University new campus project.